THE INFLUENCE OF NETWORK CAPABILITY AND INNOVATION ON KNOWLEDGE CREATION - Suganda, Uce Karna; Hadikusuma, Amran; Putro, Imam Tri (CENTRAL ASIA AND THE CAUCASUS, 2022)
Small and medium enterprises have been seen as the main engine in obtaining healthy economic growth. Despite their growth, SMEs are faced with high competition. For this reason, for business people, the right strategy can be very important to gain competitive advantage. This study aims to identify how the influence of network capability and innovation capability on knowledge creation. The results in this study indicate that network capability has a strong enough influence in building competitive advantage. Based on the results of the coefficient of determination obtained by 72.4%, this shows that the two independent variables, namely network capability and innovation capability, are important factors in forming knowledge for SMEs, especially in the city of Ciamis, while the remaining 27.6% is influenced by other variables. which were not investigated in this study.